An evidence-based training and support course for caregivers of children with foetal alcohol spectrum disorder (FASD) in New Zealand. Issue 1 (14th December 2018) - Gibbs, Anita
Abstract : Purpose: The purpose of this paper is to outline the development of an evidence-based training and support course for caregivers of children with foetal alcohol spectrum disorder (FASD) in New Zealand, and a brief evaluation undertaken. The seven-week caregiver training course takes an empowerment and advocacy orientation, and the aim is to assist caregivers who are caring for children with, or suspected to have FASD, develop greater resilience and strategies to help their families live successfully with impairments in a disabling society. Design/methodology/approach: A total of 13 parents and caregivers received a seven times two-hour weekly group programme of talks, exercises and case study discussions focused on the following objectives: an increased knowledge of FASD; an increased knowledge of successful strategies and interventions that can be used to help families; and having an opportunity to foster strong peer-support relationships with others who share the lived experience of FASD. A brief interview-based evaluation was undertaken to ascertain caregivers' views of the course, its benefits and limitations. Findings: Caregivers valued both the content and process of the training course. They highlighted that strength of the training was the delivery by experienced, professionally trained caregivers of children with FASD. They valued the opportunity to spend time with peers in similar circumstances who understood the challenges of parenting a child with FASD. Originality/value: A short evidence-based specialist training course for parents and caregivers with an empowerment and peer-support orientation is beneficial to parenting children with FASD.